(untitled) (Medico Legal Update, 2020)
A Retrospective study was conducted to assess the prevalence and risk factors of hyperemesis gravidarum among antenatal mothers in a selected tertiary care hospital, Kelambakkam, Kanchipuram District, Tamil Nadu, India. The objectives were to assess the prevalence and risk factors of hyperemesis gravidarum among antenatal mothers by collecting the data from the medical records of the patients and to find the association between risk factors of hyperemesis gravidarum with the selected demographic variables among patients with hyperemesis gravidarum. The literature review was done and organized under various aspects on studies related to prevalence and risk factors of hyperemesis gravidarum among antenatal mothers with hyperemesis gravidarum. The research approach used for the study was quantitative research approach and the design was retrospective design, 47 samples were participated in the study by using convenient sampling technique. Demographic variables are assessed by using the statistical measurement, prevalence and risk factors of hyperemesis gravidarum among antenatal mothers with hyperemesis gravidarum. The level of significance selected was p<0.05 level. The collected data was tabulated and analyzed by using SPSS Statistics -21, descriptive and inferential statistics. The study showed that there is significant association between risk factors of hyperemesis gravidarum with selected demographic variables.